A Study of Lipid Bioaccessibility in Canned Sardine (Sardina pilchardus) and Chub Mackerel (Scomber japonicus) - Garcia, T. [UNESP] (2019)
The lipid composition and bioaccessibility in canned sardine (Sardina pilchardus) and chub mackerel (Scomber japonicus) were studied. Triacylglycerols were absent from the bioaccessible fraction in both products and each FA had a different bioaccessibility level. While total fat bioaccessibility was in the 60–64% range, the bioaccessibility of ω6 PUFA and DHA was <55%. Bioaccessibility depended on canned fish product species: fat, EPA, DHA, and ω3 PUFA bioaccessibility levels seemed to be higher in canned sardine than in canned mackerel. Daily consumption of 278 g of canned mackerel or 47 g of canned sardine would ensure the recommended daily intake of EPA+ DHA.